Examining the Impact of Investment, Labor, and Zakat on Economic Growth in Indonesia: A Panel Data Approach - Syafrial Syah; Andri Soemitra; Isnaini Harahap (J-MD Jurnal Manajemen Dakwah, 2025)
This study aims to analyze the relationship between investment, labor, and zakat with economic growth in Indonesia using panel data from 33 provinces during the period 2019–2024. The study employs a quantitative approach with secondary data obtained from credible official sources, namely the Central Bureau of Statistics (BPS) and the National Zakat Agency (BAZNAS). The dependent variable used to measure economic growth is the Gross Regional Domestic Product (GRDP) at constant prices. The independent variables include realized domestic investment, total labor force, and the amount of zakat collection and distribution. Panel data regression analysis is conducted using the Fixed Effect Model (FEM), which is selected after conducting model specification tests including Chow and Hausman tests.The empirical results show that investment has a positive and significant effect on economic growth. This implies that increased investment leads to higher capital accumulation, enhanced productivity, and greater output, thereby accelerating economic growth. Labor also exhibits a positive and significant effect, indicating that a growing and active labor force plays a crucial role in supporting production and economic activities. Furthermore, zakat shows a positive and significant influence on economic growth, suggesting that zakat, as an Islamic fiscal instrument, contributes to poverty alleviation, increases consumption capacity, and supports equitable economic distribution. Overall, the study concludes that investment, labor, and zakat simultaneously have a positive and significant impact on regional economic growth in Indonesia. These findings provide important policy implications, especially in integrating Islamic economic principles into national development strategies for inclusive and sustainable growth.